2017
DOI: 10.1590/1413-812320172212.04492016
|View full text |Cite
|
Sign up to set email alerts
|

Uso de serviços odontológicos de forma regular na população de Montes Claros, MG, Brasil

Abstract: The use of dental services on a regular basis in the population of Montes Claros in the State of Minas Gerais, BrazilResumo Avaliou-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 24 publications
(38 reference statements)
1
7
0
17
Order By: Relevance
“…Regarding self-reported oral health conditions, a positive perception and absence of dental pain were associated with regular use of dental services in this study. Corroborating these findings, the literature shows that positive self-perceived oral health 12,13,17 and the absence of dental pain 13 were associated with greater regular use of dental services. These results can be explained by the fact that health perception may act as a determinant for understanding the importance of regular dentist visits and, consequently, more preventive actions result in fewer episodes of pain and a positive self-perceived oral health.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Regarding self-reported oral health conditions, a positive perception and absence of dental pain were associated with regular use of dental services in this study. Corroborating these findings, the literature shows that positive self-perceived oral health 12,13,17 and the absence of dental pain 13 were associated with greater regular use of dental services. These results can be explained by the fact that health perception may act as a determinant for understanding the importance of regular dentist visits and, consequently, more preventive actions result in fewer episodes of pain and a positive self-perceived oral health.…”
Section: Discussionmentioning
confidence: 67%
“…In Pelotas, city where UFPel is located, a population-based study conducted by Camargo et al 17 in 2009 used the same question to measure regular use of dental services and found a prevalence of 32.8% in adults. In a more recent study, also population-based, conducted in Minas Gerais, the prevalence was 35.8% for regular use of dental services among individuals over 18 years of age 13 . In this study, students who had their last dental appointment more than a year ago were classified as irregular users of dental services.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…National studies based on multiple analysis have shown that the lack of access to dental care services was more intense among individuals with older age and among those more socially vulnerable 33,34 . Extensive research on Brazilian old people has also shown that the use of public oral health services decreases with age, proving a low prevalence of access to dental care services among older people 35 .…”
Section: Discussionmentioning
confidence: 99%
“…It is common in epidemiology when searching for papers related to access to health to locate the assessment of people's access to some health professionals such as doctors, dentists, nurses, especially in primary care services, actions and programs 3,4 . These studies are frequent in the Unified Health System (SUS), and evaluate the coverage, process and effectiveness of services to the population.…”
Section: Introductionmentioning
confidence: 99%